Essentials of online course design a standards-based guide - Vai, Marjorie; Sosulski, Kristen (Essentials of online learning series, 2016)
In spite of the proliferation of online learning, creating online courses can still evoke a good deal of frustration, negativity, and wariness in those who need to create them. The second edition of Essentials of Online Course Design takes a fresh, thoughtfully designed, step-by-step approach to online course development. At its core is a set of standards that are based on best practices in the field of online learning and teaching. Pedagogical, organizational, and visual design principles are presented and modeled throughout the book, and users will quickly learn from the guide's hands-on approach. The course design process begins with the elements of a classroom syllabus which, after a series of guided steps, easily evolve into an online course outline. The guide's key features include: a practical approach informed by theory; clean interior design that offers straightforward guidance from page one; clear and jargon-free language; examples, screenshots, and illustrations to clarify and support the text; a checklist of online course design standards that readers can use to self-evaluate; a conpanion website with examples, adaptable templates, interactive learning features, and online resources. Essentials of Online Course Design serves as a best practice model for designing online courses. After reading this book, readers will find that preparing for online teaching is a satisfying and engaging experience. The core issue is simply good design: pedagogical, organizational, and visual.